The Influence of Curriculum Change From KBK Into KTSP to Student Achievement of SMP N 02 Pekalongan - SHOLIKHATUN KHASANAH (Jurusan tarbiyah- Pendidikan Agama Islam - STAIN Pekalongan, 2009)
The background of this research are Indonesian government changed the curiculum with KBK into KTSP. KTSP can help student passing the exam and increasing their final grade. This research is based on the problems as follows does curriculum change fraom KBK into KTSP increase or decrease student achievement, and what are the factors cause change, increasing or decreasing or unchanged final mark of student. The approach of this research is qualitative approach with field research. The result of research show there is no significance difference between student final grade on KBK and KTSP, menas the cange curriculum from KBK into KTSP doesn’t influence student achievement of SMP N 02 Pekalongan. Some factors cause this case are internal factor is teacher paradigm which thinks that there is no big difference between KBK and KTSP and only little change of teacher creativity. External factors are school has good students from the hard selection done every year and there is no difference between teacher prosperity on KBK and KTSP.